Effects of Toll-Like Receptors 3 and 4 in the Osteogenesis of Stem Cells - Chen Qi; Xu Xiaofeng; Wang Xiaoguang (Hindawi Limited, 2014)
Objective. To investigate the effects of Toll-like receptors in stem cell osteogenesis. Methods. Bone marrow mesenchymal stem cells (BMSCs) were divided into the blank group, the TLR-3 activated group, and the TLR-4 activated group. After 10 days' osteogenic-promoting culture, expression of type I collagen and osteocalcin was determined by Western blot. Osteoblasts (OBs) were also divided into three groups mentioned above. Alkaline phosphatase (ALP) and alizarin red staining were performed after 10 days' ossification-inducing culture. The expression of β-catenin was investigated by Western blot. Results. Both the TLR-3 and TLR-4 activated groups had increased expression of type I collagen and osteocalcin; the effect of TLR-4 was stronger. The intensity of alizarin red and ALP staining was strongest in the TLR-3 activated group and weakest in the TLR-4 activated group. Activation of TLR-4 decreased the expression of β-catenin, whilst activation of TLR-3 did not affect the expression of β-catenin. Discussion. This study suggested that both TLR-3 and -4 promoted differentiation of BMSCs to OBs. TLR-3 had an inducing effect on the ossification of OBs to osteocytes, whilst the effect of TLR-4 was the opposite because of its inhibitory effect on the Wnt signaling pathway.